Respuesta :
x
+
2
=
2
(
4
x
+
1
)
Explanation:
Factor
8
x
+
2
.
Factor out the GCF
2
.
2
(
8
4
x
2
1
+
2
1
2
1
)
Simplify.
2
(
4
x
+
1
)
+
2
=
2
(
4
x
+
1
)
Explanation:
Factor
8
x
+
2
.
Factor out the GCF
2
.
2
(
8
4
x
2
1
+
2
1
2
1
)
Simplify.
2
(
4
x
+
1
)
The expression 8x+2 factored using the GCF is 2(4x + 1)
Equations are expressions separated by an equal sign
Given the expression 8x + 2
First we need to find the factors of each terms
8x = 2 * 4 * x
2 = 2 * 1
From bot factors, we can see that 2 is common. Factoring out 2 from the expression will give;
8x + 2 = 2(4x + 1)
Hence the expression 8x+2 factored using the GCF is 2(4x + 1)
Learn more here: https://brainly.com/question/219464